2017
DOI: 10.1039/c7cc02093g
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanoparticles socketed in situ into copper phyllosilicate nanotubes with enhanced performance for chemoselective hydrogenation of esters

Abstract: Copper nanoparticles exsoluted in situ under a reducing atmosphere at elevated temperatures are socketed into the parent copper phyllosilicate nanotubes and exhibit excellent catalytic performance and superior stability for the selective hydrogenation of various esters to alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…The TEM images of CuPSs were also recorded (Figure S4); however, Cu particle could not be identified clearly. Formation of immobilized Cu during the reduction treatment of CuPSs (known as exsolution) is likely to cause the differences of resolutions of Cu particles between CuPSs and reduced CuPSs …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TEM images of CuPSs were also recorded (Figure S4); however, Cu particle could not be identified clearly. Formation of immobilized Cu during the reduction treatment of CuPSs (known as exsolution) is likely to cause the differences of resolutions of Cu particles between CuPSs and reduced CuPSs …”
Section: Resultsmentioning
confidence: 99%
“…The decreases of (Cu/Si) surf ratios of reduced CuPSs indicated that exsolution of Cu from phyllosilicate structure could be promoted during reduction. Exsoluted Cu formed immobilized Cu particles on the surface, resulting in lower Cu‐to‐Si XPS intensity ratios of reduced CuPSs than those of CuPSs. The schematic diagram of the formation of exsoluted Cu particles through the reduction of CuPS was shown in Figure S5 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Bisquert and Kern proposed the model including diffusion coupled with a homogeneous reaction with a continuity equation (as shown in eqn (S1) †). [56][57][58] In this equivalent circuit model, the equivalent circuit included components of R1 (series resistance), R2 (resistance of Pt counter electrode), CPE1 (double layer capacitance of Pt counter electrode) and DX1 (a complex electronic component composed with r t , r r , and C p as shown in Fig. S1 †).…”
Section: Eis Analysismentioning
confidence: 99%
“…Such materials play an important role in catalytic processes like water gas shift, partial oxidation and reforming of methane (dry and wet), alkene hydrogenation, alkane hydrogenolysis, higher alcohol synthesis, and Fischer‐Tropsch synthesis . The in situ segregation strategy is also exploited for perovskite‐type oxides central to solid oxide fuel cells (SOFC) and for heterogeneous catalytic application for soot combustion even some homogeneous application for selective hydrogenations . Moreover, application of perovskite‐type oxides in automotive exhaust catalysis has been demonstrated extensively .…”
Section: Introductionmentioning
confidence: 99%